Optimizing The Role Of Teachers In Fostering Student Discipline - Nafisah Masruroh; Feriska Lestianti (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to analyze the optimization of teachers' roles in fostering student discipline at SMP Nurul Jadid. The research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving the principal, teachers, school counselors, and students. Data were analyzed through data reduction, data display, and conclusion verification to ensure the validity of the findings. The results indicate that teachers play a strategic role in fostering student discipline through exemplary behavior, guidance, persuasive communication, and humanistic interpersonal approaches. Teachers consistently reinforce disciplined behavior through habituation, motivation, and responsive counseling services. The behavioristic approach is implemented through the provision of stimuli, reinforcement, and the habituation of disciplined behavior, while the humanistic approach is applied through empathetic relationships, self-reflection, and individualized guidance for students. In addition, school counseling services are conducted in an educational and continuous manner, enabling students to recognize their mistakes and independently improve their behavior. Supporting factors for the development of student discipline include positive interpersonal relationships, a conducive school environment, and a sustainable guidance system. Meanwhile, inhibiting factors include students' low self-awareness, peer influence, and inconsistencies in the implementation of school regulations. The study concludes that optimizing teachers' roles through the integration of behavioristic and humanistic approaches is effective in enhancing students' self-awareness and discipline within the school environment.